Study on Characteristic of Motorcycle Suspension - Francis, Brandon Vico; bin Azizul, Muhammad Asri; bin Sulaiman, Syabillah (Journal of Automotive Powertrain and Transportation Technology, 2021)
Generally, the motorcycle has the same system as a vehicle. Its main function of the suspension system is to provide good driving comfort, better handling, isolating the noise, bump and vibration from the road condition. The passenger of motorcycle also experienced the different effect such as handling and ride comfort from different velocity of the motorcycle. The main objective of this study is to develop the simulation of a motorcycle passive suspension system and to investigates the effect of ride comfort of the motorcycle by apply different speed using vehicle model analysis. All the simulations were carried using Matlab\Simulink software and the simulation model were conducted by applying different of speed which is 20 km/h, 30 km/h and 40 km/h when hit the bump. The finding of the result from the simulation progress showed that the effect of both the distribution of spring-damping supported mass. The finding results also showed that the half-car model for passive suspension system of a vehicle can be used on a motorcycle by using the appropriate suspension component and bump dimension parameter to be simulated in the Matlab\Simulink software.